Pemberdayaan Keagamaan dan Sosial Di Masyarakat Melalui TK/TPA, Pembacaan Surah Al-Waqiah, Yaasin Dan Al-Kahfi, Serta Pelatihan Pengurusan Jenazah - Indri Karadona, Rosika; Majid, Asmarani; Zuud Noer Algemsi, Muh.; Ryzchi Yuliananigsih, Andi; Jumaeni, Jumaeni; Azmi Rauf, Ulil; Ikbal, Muh. (Tasnim Journal for Community Service, 2025)
Religious and social empowerment has an important role in shaping individual character and improving the quality of life in society. The Community Service Program (KKN) in Tabbinjai Village, Kuncio Pao District, Gowa Regency, carries out various activities that focus on religious and social aspects. Some of the main programs implemented include managing the Al-Qur'an Education Park (TPA), regular reading of Surah Al-Waqiah and Al-Kahf, as well as training in handling corpses. This program aims to increase public understanding of Islamic values, strengthen social correlation, and build a more religious and harmonious environment. The approach used in this activity is Participatory Action Research (PAR), which involves active participation of students and the community in every stage of implementation. The methods applied include interviews, active learning, lectures and demonstrations to ensure program effectiveness. The results of this activity show high enthusiasm and community involvement, especially in learning the Koran for children, routine religious activities, and education on corpse management. With this program, it is hoped that there will be an increase in awareness and quality of religious life in Tabbinjai Village, as well as the formation of a young generation who has good religious understanding and strong social values.